The Use Of Probing-Prompting Learning Strategy To Improve Biology Learning Outcomes Of Class XI IPA 3 Students At SMA Negeri 5 Kendari - Alfasri Ahmad (Journal of Biological Science and Education, 2019)
The purpose of the study was to improve the biology learning outcomes of students in class XI IPA 3 at SMA Negeri 5 Kendari. This study was conducted in the second semester of the academic year 2013/2014. The research design of this study was a Classroom Action Research (CAR) with three learning cycles. Each cycle goes through four stages: (1) planning; (2) implementing actions; (3) observation and evaluation; and (4) reflection. The data source of this study were students who were measured by using the learning outcomes test of the cycle I, cycle II, and cycle III. The data obtained were analyzed using descriptive analysis. Biology learning outcomes of Class XI IPA3 students at SMA Negeri 5 Kendari taught using the Probing-Prompting learning strategy showed an increase in each cycle namely cycle I by 71.78%, cycle II by 86.35%, and in cycle III it reached an average of 87 47%. Based on the results of the study concluded that the Probing-Prompting learning strategy could improve the learning outcomes of biology students of class XI IPA3 SMA Negeri 5 Kendari.  Keywords: Probing-Prompting Strategies, Learning Outcomes